Chemical and mechanical characterization of thermally modified Gmelina arborea wood - Minkah, Maxidite Amankwaah (Les (Ljubljana), 2021)
Gmelina arborea (Roxb. ex. Sm.) wood samples were thermally modified at 180 °C, 200 °C and 220 °C for 3 h, by employing a process similar to ThermoWood. The resulting effects on the basic chemical composition and mechanical properties were determined. The results were analyzed statistically with ANOVA, and Least Square Deviation was used to compare means. Generally, after the thermal modification (TM) process, the cellulose, hemicelluloses and extractives content decreased significantly. By contrast, lignin proportions increased significantly. Untreated wood and samples modified at 180 °C indicated comparable modulus of elasticity (MOE), modulus of rupture (MOR), degree of integrity (I), fine fraction (F) and resistance to impact milling (RIM). Noteworthy reductions however occurred at 200 °C and 220 °C. Significant increases in Brinell hardness (BH) took place at 180 °C, recording a high decrease at 220 °C. Gmelina arborea could be modified suitably at 180 °C for structural and other purposes. To take advantage of other improved properties, modification at 200 °C could be employed for non-structural uses.
Keywords: HEMI; high-energy multiple impact; les; lesne glive; odpornost proti udarnemu mletju; razkroj; resistance to impact milling; RIM; static bending; statični upogib; termična modifikacija; thermal modification; večkratni visokoenergijski udarci; wood